Controlled-Release Fertilizers for Potato Production in Florida - Guodong Liu; Eric H. Simonne; Yuncong Li; Chad M. Hutchinson; Mark Warren; Steven Lands (EDIS)
The recent emphasis on the development of vegetable production best management practices has prompted a re-examination of fertilization practices in Florida potato production in the St. Johns River watershed. The numbers provided in this revised 5-page fact sheet serve as a starting point for discussion about the value of using controlled-release fertilizers, which can be a win-win-win opportunity for producers, manufacturers, and regulatory agencies by helping all meet their production, business, and environmental goals. Written by Guodong Liu, Eric H. Simonne, Yuncong Li, Chad M. Hutchinson, Mark Warren, and Steven Lands, and published by the UF Department of Horticultural Sciences, October 2011. (UF/IFAS Photo by Tyler Jones)